Elevated MR-proANP plasma concentrations are associated with sepsis and predict mortality in critically ill patients - Yagmur, Eray (J Transl Med, 2019)
BACKGROUND AND AIMS: Mid-regional pro atrial natriuretic peptide (MR-proANP) is an established biomarker for heart failure, based on its key role in regulating homeostasis of water balance and blood pressure. The aim of the study was to determine the value of MR-proANP as a clinical biomarker in critical illness and/or sepsis. Upon admission to the medical intensive care unit (ICU), we investigated MR-proANP plasma concentrations in 217 critically ill patients (144 with sepsis, 73 without sepsis). Results were compared with 65 healthy controls. RESULTS: MR-proANP plasma levels were significantly elevated in critically ill patients, when compared to healthy controls. Notably, MR-proANP levels were significantly higher in ICU patients with sepsis. MR-proANP levels were not associated with metabolic comorbidities like diabetes or obesity. In critically ill patients, MR-proANP plasma concentrations correlated with inflammatory cytokines, markers of organ dysfunction and several adipocytokines, such as resistin, retinol-binding protein 4 (RBP4) and adiponectin. Importantly, high MR-proANP plasma levels were associated with mortality, as MR-proANP levels above 227.0 pmol/l indicated a particularly increased mortality risk in ICU patients. The association between MR-proANP and mortality was independent of single organ failure and inflammation markers. CONCLUSION: Our study emphasizes the role of circulating MR-proANP as a biomarker in critically ill patients, in which high MR-proANP indicates organ dysfunction, sepsis and mortality risk. The association between high MR-proANP and inflammatory as well as adipose tissue-derived endocrine mediators warrants further pathophysiological investigations.